Parametric Study on Wing-Lambda-Shock Formation - Sirikorn Chainok; Thanapol Rungroch; Pattarasuda Chairach; Prasert Prapamonthon; Soemsak Yooyen; Bo Yin; Guowei Yang; Shengjun Ju (My University, 2021)
Abstract It is well-known that a wing is one of the most important parts of an aircraft as it is used to generate lift force. According to a wing moving at sufficiently high subsonic speeds, the flow speed on the wing’s upper surface can be supersonic due to acceleration through the curvature-created suction, thereby forming a shock wave in a lambda shape. Additionally, the lambda shock can interact with the boundary layer flow. These phenomena relate to disturbances in the flow field, including flow separation, thus causing undesirable effects on lift production. Hence, a better understanding of the phenomenon of wing-lambda-shock formation and its nature is essential. This study presents a numerical investigation of the lambda-shock formation on an ONERA M6 wing, which is known as a swept, semi-span wing with no twist, under parametric effects of angle-of-attack, and free-stream Mach number, which is increased up to the supersonic regime. The pressure coefficients obtained by simulations are validated by open data. Then, numerical results in terms of the local pressure coefficient, local Mach number, averaged lift and drag coefficients, and λ-shape characteristics based on Mach number and pressure coefficients are discussed under an investigated range of the parameters. Results show that the angle-of-attack and free-stream Mach number can affect the lambda shock formation on the wing upper surface physically. Specifically, an iso-sonic surface with lambda shock waves is disturbed when the angle-of-attack and free-stream Mach number vary in an investigated range. This also affects lift and drag coefficients of the wing.
Keywords: Lift (data mining); Computational Fluid Dynamics and Aerodynamics